2021
DOI: 10.3389/fimmu.2020.563473
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocyte-Specific Biomarkers Associated With Preterm Birth and Bronchopulmonary Dysplasia

Abstract: Many premature babies who are born with neonatal respiratory distress syndrome (RDS) go on to develop Bronchopulmonary Dysplasia (BPD) and later Post-Prematurity Respiratory Disease (PRD) at one year corrected age, characterized by persistent or recurrent lower respiratory tract symptoms frequently related to inflammation and viral infection. Transcriptomic profiles were generated from sorted peripheral blood CD8+ T cells of preterm and full-term infants enrolled with consent in the NHLBI Prematurity and Respi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 77 publications
0
15
0
Order By: Relevance
“…10 A recent study has further identified a set of differentially expressed genes and the dysregulated pathways associated with T cell activation in BPD subjects. 11 In recent years, bioinformatics approaches have been attempted to unveil the underlying pathways involved in BPD development. Angiogenesis and inflammation were considered as important biological changes that contributed to the BPD development, and the expression of interleukin 6 mRNA was observed pronouncedly increased in early BPD.…”
Section: Introductionmentioning
confidence: 99%
“…10 A recent study has further identified a set of differentially expressed genes and the dysregulated pathways associated with T cell activation in BPD subjects. 11 In recent years, bioinformatics approaches have been attempted to unveil the underlying pathways involved in BPD development. Angiogenesis and inflammation were considered as important biological changes that contributed to the BPD development, and the expression of interleukin 6 mRNA was observed pronouncedly increased in early BPD.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is possible that lower expression of this miRNA in severe BPD infants is associated with fibrotic phenotypes in severe BPD. It is worthwhile to mention that the Hippo pathway is a powerful regulator of lung development, cell differentiation, and tissue regeneration and homeostasis, and has been found dysregulated in lymphocytes of patients with BPD [61,62]. Therefore, the role of miR-15a and the Hippo pathway in mechanisms leading to BPD severity warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The novel meta-analysis loci associated with gestational duration, such as variants in GNAQ and KCNN2 , comprised further intriguing candidates. GNAQ (protein subunit alpha q) plays a role in survival of immune cells and was identified as part of a transcriptomic signature related to human labor in the choriodecidua 28,29 . KCNN2 (potassium calcium-activated channel subfamily N member 2) has no obvious connection to pregnancy-related regulation, but KCNN3 , another molecule in the KCNN family of potassium channel genes, plays a role in uterine function 30 .…”
Section: Discussionmentioning
confidence: 99%